Red, white, and true : stories from veterans and families, World War II to present - Crow, Tracy (Potomac Books, an imprint of the University of Nebraska Press, 2014)
A collection of 32 essays written by both veterans and family members describing their experiences from conflicts spanning World War II to Afghanistan.